2013
DOI: 10.1128/jb.01209-13
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Escherichia coli K-12 Growth Observation and Gene Essentiality Data to the EcoCyc Database

Abstract: The sets of compounds that can support growth of an organism are defined by the presence of transporters and metabolic pathways that convert nutrient sources into cellular components and energy for growth. A collection of known nutrient sources can therefore serve both as an impetus for investigating new metabolic pathways and transporters and as a reference for computational modeling of known metabolic pathways. To establish such a collection for Escherichia coli K-12, we have integrated data on the growth or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
(7 reference statements)
0
9
0
1
Order By: Relevance
“… E. coli has the remarkable ability to use many carbon sources for growth which makes it possible to exhaustively probe central metabolism pathways using different carbon sources. Since methodologies differ from lab to lab, unifying different gene essentiality data sets has been difficult ( 33 ). This speaks to the need for more comprehensive data sets that explore a large number of conditions using the same strains and methodology.…”
Section: Introductionmentioning
confidence: 99%
“… E. coli has the remarkable ability to use many carbon sources for growth which makes it possible to exhaustively probe central metabolism pathways using different carbon sources. Since methodologies differ from lab to lab, unifying different gene essentiality data sets has been difficult ( 33 ). This speaks to the need for more comprehensive data sets that explore a large number of conditions using the same strains and methodology.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that a loss of bacterial viability proportional to mutagenic potency beyond a mutation rate of ∼4 × 10 −7 substitutions per bp per generation, corresponding to an average of ∼1.9 substitutions per genome per generation. Given that ∼10–30% of the E. coli genome has been estimated to be essential 26 , this mutation rate threshold corresponds to ∼0.2–0.6 mutations in an essential gene/generation.…”
Section: Resultsmentioning
confidence: 99%
“…Another factor contributing to the large number of food molecules are environmental adaptations of E. coli . As recently summarized by Mackie et al [ 42 ] E. coli can grow under different conditions, for example, under aerobic and anaerobic conditions, or using different carbon sources. The extended food set allows for all of these alternative pathways to be functioning within the RAF network.…”
Section: Resultsmentioning
confidence: 99%
“…A second food set was created based on the laboratory conditions given for E. coli growth on glucose-6-phosphate and glucose as in [ 42 ]. The reactions included in the resulting RAF network were mapped to E. coli Kegg pathways [ 43 ].…”
Section: Methodsmentioning
confidence: 99%